(untitled) (مجلة الفاروق للعلوم, 2026)
Al-6061 is one of those workhorse alloys you find everywhere, from aircraft frames to automotive panels, and for good reason—it offers a strength-to-weight ratio that makes engineers quite happy. But the conventional T6 heat treatment, the gold standard for decades, pushes hardness and tensile strength up at the expense of ductility, and in many real-world applications that trade-off is simply unacceptable. This study explores whether a gradual, stepwise heat treatment can break that compromise. Specimens of Al-6061 were solution-treated at 530 °C and subjected to two aging routes: conventional single-step aging at 175 °C for 8 hours, and a three-step gradual aging protocol at 140 °C, 160 °C, and 180 °C for 3, 3, and 2 hours, respectively. The gradually treated specimens exhibited a 7.5% improvement in ultimate tensile strength (285 ± 5 MPa vs. 265 ± 4 MPa), a 9.2% increase in hardness (107 ± 3 HV vs. 98 ± 2 HV), and retained comparable ductility at 14.2 ± 0.8% elongation versus 14.8 ± 1.0% for the conventional route. Fractographic analysis revealed more uniform dimple distributions in gradually treated specimens. These findings suggest that gradual heat treatment is a genuinely viable alternative for applications requiring strength without sacrificing formability.